Security and privacy in cyber-physical systems : foundations, principles, and applications - Song, Houbing; Fink, Glenn A.; Jeschke, Sabina; IEEE Xplore (Online Service); Wiley (Chichester, UK ; Hoboken, NJ : John Wiley & Sons, 2017)
The premier source of information on CPS security and privacy theory, guiding principles, and state-of-the-art applications Written by a team of experts at the forefront of the cyber-physical systems (CPS) revolution, this book provides an in-depth look at security and privacy, two of the most critical challenges facing both the CPS research and development community and ICT professionals. It explores, in depth, the key technical, social, and legal issues at stake, and it provides readers with the information they need to advance research and development in this exciting area. Cyber-physical systems (CPS) are engineered systems that are built from, and depend upon the seamless integration of computational algorithms and physical components. Advances in CPS will enable capability, adaptability, scalability, resiliency, safety, security, and usability far in excess of what today's simple embedded systems can provide. Just as the Internet revolutionized the way we interact with information, CPS technology has already begun to transform the way people interact with engineered systems. In the years ahead, smart CPS will drive innovation and competition across industry sectors, from agriculture, energy, and transportation, to architecture, healthcare, and manufacturing. . A long-awaited review for all those concerned with the fundamental concepts and the state-of-the-art in security and privacy in CPS. Provides comprehensive coverage of the technical issues affecting hardware and software in infrastructure components, as well as the blending of such systems with personal CPS. Discusses various application domains, including energy, medicine, transportation, physical infrastructure, agriculture, smart cities, and many more. Includes case studies and tutorials and supports university courses such as those in cybersecurity and privacy and CPS engineering and programming A priceless source of practical information and inspiration, Security and Privacy in Cyber-Physical Systems: Foundations, Principles, and Applications is certain to have a profound impact on ongoing R&D and education at the confluence of security, privacy, and CPS.
Overview of security and privacy in cyber-physical systems -- Network security and privacy for cyber-physical systems -- Tutorial on information theoretic metrics quantifying privacy in cyber-physical systems -- Cyber-physical systems and national security concerns -- Legal considerations of cyber-physical systems and the Internet of Things -- Key management -- Secure registration and remote attestation of IoT devices joining the cloud : the Stack4Things case of study -- Context awareness for adaptive access control management in IoT environments -- Data privacy issues in distributed security monitoring system -- Privacy protection for cloud-based robotic networks -- Network coding technique : security challenges and applications -- Lightweight crypto and security -- Cyber-physical vulnerabilities of wireless sensor networks in smart cities -- Towards detecting data integrity attacks in smart grid -- Survey on data security and privacy in wireless sensor systems for health -- Security of smart buildings -- The internet of postal things : making the postal infrastructure smarter -- Security and privacy issues in the internet of cows -- Admission control based load protection in the smart grid.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web
Description based on PDF viewed 10/30/2017.
Keywords: Computer networks -- Security measures; Data protection; Electronic books